2013
DOI: 10.1161/circoutcomes.111.000072
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk of Ischemic and Bleeding Events in Acute Coronary Syndromes

Abstract: . In-hospital care and events up to 6 months were assessed. At least 2 clinicians involved in patient care estimated the untreated risk and change in risk with each therapy. Physician risk assessment and objective risk measures (eg, Global Registry of Acute Coronary Events [GRACE] score) for death, death/myocardial infarction, and bleeding events were compared using the c statistic and integrated discrimination improvement. In total, 1542 patients and 4230 patient-specific physician estimates were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 36 publications
3
27
0
3
Order By: Relevance
“…13,15 Objective risk assessment using the GRACE risk score provided superior risk discrimination to physician-perceived risk for 6-month mortality in patients with ACS in the Perceived Risk of Ischemic and Bleeding Events in Acute Coronary Syndrome Patients (PREDICT) study. 49 Here, physicians were shown to overestimate the risk of 6-month mortality among patients with a low GRACE score and underestimate risk among those with a high GRACE score, consistent with the treatment-risk paradox. 49 Patients with NSTEMI at high ischemic risk were also not treated optimally in the Myocardial Ischaemia National Audit Project (MINAP) registry, in which the use of guideline-indicated care for patients with NSTEMI decreased with increasing GRACE risk score, even though optimal guideline-indicated care was associated with greater survival gains for high-risk patients.…”
Section: Patient Characteristicssupporting
confidence: 60%
See 2 more Smart Citations
“…13,15 Objective risk assessment using the GRACE risk score provided superior risk discrimination to physician-perceived risk for 6-month mortality in patients with ACS in the Perceived Risk of Ischemic and Bleeding Events in Acute Coronary Syndrome Patients (PREDICT) study. 49 Here, physicians were shown to overestimate the risk of 6-month mortality among patients with a low GRACE score and underestimate risk among those with a high GRACE score, consistent with the treatment-risk paradox. 49 Patients with NSTEMI at high ischemic risk were also not treated optimally in the Myocardial Ischaemia National Audit Project (MINAP) registry, in which the use of guideline-indicated care for patients with NSTEMI decreased with increasing GRACE risk score, even though optimal guideline-indicated care was associated with greater survival gains for high-risk patients.…”
Section: Patient Characteristicssupporting
confidence: 60%
“…Objective risk assessment using the GRACE risk score provided superior risk discrimination to physician‐perceived risk for 6‐month mortality in patients with ACS in the Perceived Risk of Ischemic and Bleeding Events in Acute Coronary Syndrome Patients (PREDICT) study . Here, physicians were shown to overestimate the risk of 6‐month mortality among patients with a low GRACE score and underestimate risk among those with a high GRACE score, consistent with the treatment‐risk paradox …”
Section: Challenges For the Treatment Of Patients With Nstemimentioning
confidence: 52%
See 1 more Smart Citation
“…In fact, comparative studies of the two approaches have consistently suggested greater overall accuracy when clinicians rely on actuarial information over anecdotal evidence in treatment decisions. 3335 Kahneman, the Noble Prize-winning psychologist, describes decision-making as being comprised of 2 systems, a fast-thinking, intuitive system that rapidly makes decisions based on associations with past experiences, and a slow-working, logical, reasoning system that incorporates evidence to make a more rational decision. 36 The first, fast-thinking system is much easier and less stressful to use and is vastly preferred over the more deliberate second system.…”
Section: Discussionmentioning
confidence: 99%
“…Risk models are an important part of AMI care because clinicians may underestimate the risk of adverse clinical outcomes when relying on implicit risk assessments alone, particularly in older adults. 68 …”
Section: Introduction1mentioning
confidence: 99%